Risk factors and the relation of lactic acid to neonatal mortality in the first week of life - Rodríguez Balderrama, Isaías; Ostia Garza, Patricia Johane; Villarreal Parra, Rosa Delia; Tijerina Guajardo, Mercedes (UANL. Facultad de Medicina, 2016)
To determine the relationship between lactic acid levels and neonatal mortality in the first week of life, in patients admitted to the Neonatal Intensive Care Unit (NICU) of the ‘‘Dr. José E. González’’ University Hospital. Material and methods: Prospective, observational and diagnostic test performed in the neonatal ward of the ‘‘Dr. José Eleuterio González’’ University Hospital. We included all live preterm infants on mechanical ventilation who were admitted to the NICU from November 1, 2011 to October 31, 2012. Results: One hundred and fifty four patients met the inclusion criteria. At 72 h, we found that the best sensitivity (95%) was when lactate was less than 1.5 mmol/l and the best specificity (89%) was present when lactate levels were greater than 2.5 mmol/l. The pH <7.25 had a sensitivity of 76% and specificity of 96%. At 168 h (7 days) we found that the best sensitivity (91%) was when lactate levels were less than 1.5 mmol/l, and that the best specificity (96%) was when lactate levels were greater than 2.5 mmol/l. We found that the pH <7.25 had a sensitivity of 36% and specificity of 91%. Conclusion: The lactate serum, at 1.5 mmol/l, has a sensitivity (to be killed) of 95% on the third day and 91% on the seventh day. When the pH is greater than 7.25 there is a specificity (to be alive) of 96% on the third day and 91% on the seventh day. 67% of the dead were under 1500 g, and were 61% under 28 gestational weeks.